Optical Fiber Communication Conference 2016
DOI: 10.1364/ofc.2016.tu2k.2
|View full text |Cite
|
Sign up to set email alerts
|

InP-based Optical Comb-locked Tunable Transmitter

Abstract: We demonstrate a comb-based transmitter with a potential to be integrated on a single InP photonic chip. Nyquist-shaped polarization-multiplexed 16QAM/64QAM signals are generated and transmitted over 300-km of SMF-28.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The extracted tones are modulated individually via IQ modulators for signal generation. Due to the fixed tone spacing, the guard band can be minimized [7]. The phase coherent sub-channels can also be synthesized to become a large bandwidth super channel provided the phase between different paths are locked [95].…”
Section: A Coherent Super-channel Transmittermentioning
confidence: 99%
See 1 more Smart Citation
“…The extracted tones are modulated individually via IQ modulators for signal generation. Due to the fixed tone spacing, the guard band can be minimized [7]. The phase coherent sub-channels can also be synthesized to become a large bandwidth super channel provided the phase between different paths are locked [95].…”
Section: A Coherent Super-channel Transmittermentioning
confidence: 99%
“…The tone recovery with low comb power allows the comb to be distributed to a large number (e.g., 100s) of racks for both short and long-reach coherent communications. In [7], we OIL a telecom-grade InPbased digital supermode distributed Bragg reflector (DS-DBR) tunable laser to a 25-GHz-spaced frequency comb, showing C-band tunable tone extraction with a simultaneous linewidth reduction from 1.5 MHz to 4 kHz. Importantly, our experiment showed that the key building blocks (inc. comb [96], tunable laser, modulator) are readily achievable on the InP photonic integration platform.…”
Section: A Coherent Super-channel Transmittermentioning
confidence: 99%
“…To compensate for the residual chirp induced amplitude-phase modulation, we measured the amplitude-phase response of OIL-DMLs and proposed a data set based method to compensate for the nonlinear field response for the first time. This approach can be applied to other semiconductor modulators such as InP IQ modulator [27] to compensate for residual amplitude-phase modulation, as we have demonstrated in [28].…”
Section: B Discussionmentioning
confidence: 99%
“…In many applications, phase synchronization over as large a bandwidth as possible is required. An example is Slave laser linewidth narrowing using a narrow-linewidth Master laser [ 5], or extraction of a single tone of an Optical Frequency Comb (which plays the role of the Master signal [ 6]), as shown in Fig. 1b.…”
Section: Low Oil Ratiomentioning
confidence: 99%